Patient survival and limb salvage after shark attack with major vascular injury: A case report - Ayman Khalil (Elsevier, 2021)
Shark attacks are rare unique pathological processes. Some of them represent devastating injuries with a high morbidity and significant mortality. Related published articles are limited. The increased human interaction within the environment of sharks is the cause of rising incidence of such attacks. This study reported a case of level 4 shark injuries (shark-induced trauma scale) in a 33-year-old male patient, who presented with an extensive injury of the right lower limb with the characteristic features of shark bite. At admission the patient was in a state of shock with profuse bleeding that was controlled by tourniquet. The patient was resuscitated according to the advanced trauma life support. Clinical examination showed hard signs of vascular injury with absent pedal pulse, associated neurological deficits and severance at the knee joint. Prompt vascular intervention after resuscitation was performed to manage the major vascular injuries, together with proper washout and debridement of all the necrotic tissues under strong antibiotic coverage to prevent infection. After that, the patient underwent sequenced plastic, orthopedic, and neurological interventions. Strict follow-up was conducted, which showed that the patient was saved and achieved a functioning limb. This study aims to highlight the management of level 4 shark injuries, which are considered serious and challenging with a high fatality rate and a great risk of amputation due to the associated major vascular injuries. Immediate well organized management plan is crucial. Prompt resuscitation and surgical intervention by a highly-skilled medical team are required to improve the chance of patient survival and limb salvage.